PSMA PET/CT for prostate cancer diagnosis: current applications and future directions - Zhengang Shen; Zeng Li; Yunlong Li; Xiaodi Tang; Jiayi Lu; Li Chen; Zhu Zhong Cheng; Hong Liao; Shukui Zhou (Journal of Cancer Research and Clinical Oncology)
Abstract Prostate cancer (PCa) requires improved diagnostic strategies beyond conventional imaging. This review aimed to evaluate the role of prostate-specific membrane antigen positron emission tomography/computed tomography (PSMA PET/CT) in diagnosing advanced PCa. The review analyzed the diagnostic performance of PSMA PET/CT in various clinical contexts, including locoregional staging, extracapsular extension (ECE), seminal vesicle invasion (SVI), pelvic lymph node metastases, distant metastases, and biochemical recurrence (BCR). Further, challenges such as PSMA-negative tumors, need for standardized protocols, and potential of emerging imaging targets (neurotensin receptor 1 and fibroblast activation proteins) were reviewed. The role of artificial intelligence (AI) and advancements in tracer development were explored. PSMA PET/CT demonstrated exceptional specificity for locoregional staging, ECE, and SVI while reducing unnecessary biopsies and optimizing biopsy strategies. The diagnostic accuracy for pelvic lymph node metastases was higher with PSMA PET/CT than with traditional methods, although sensitivity for micrometastasis detection remained challenging. For distant metastases, PSMA PET/CT outperformed bone scintigraphy (BS) and conventional imaging, particularly in identifying bone and atypical lesions. In BCR cases, PSMA PET/CT reliably detected recurrent lesions at low prostate-specific antigen levels, significantly influencing treatment strategies. The review findings indicate that PSMA PET/CT is a superior diagnostic tool for PCa due to its high specificity and accuracy. Despite limitations such as PSMA-negative tumors and sensitivity challenges, advancements in AI, novel imaging targets, and affordable tracer development hold promise for broader clinical adoption. This review underscores the transformative potential of PSMA PET/CT in PCa diagnosis and management, advocating for ongoing research and protocol standardization.